2020
DOI: 10.1088/2053-1591/ab6c1d
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the mechanical, wear and corrosion behaviour of stir casted aluminium 6061 hybrid composites through the incorporation of boron nitride and aluminium oxide particles

Abstract: This research paper portrays the enrichment of mechanical, wear and corrosion properties of the Aluminium 6061 matrix composite by incorporating hybrid reinforcements. Aluminium 6061 alloy is stir casted with different proportions of boron nitride (BN), Aluminium oxide (Al 2 O 3 ) and graphite particles. Tensile test reveals that the tensile strength and ductility for the Al 6061-30 BN -10Al 2 O 3 -5C is improved due to the presence of higher BN content along with 10% Al 2 O 3 . Significant improvement in micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…This is such that the counter faces in the composites and the abrasive opposing material are separated by a layer of protecting material [110][111][112]. Gopinath et al [113] noticed the highest enhanced wear resistance in AA6061%-30%BN-10%Al 2 O 3 -5%Gr hybrid composite over all other materials regardless of the test conditions. According to a study by Sharma et al [114], sillimanite-reinforced composite offered enhanced wear resistance over the monolithic alloy.…”
Section: Influence Of Particle Reinforcementmentioning
confidence: 99%
“…This is such that the counter faces in the composites and the abrasive opposing material are separated by a layer of protecting material [110][111][112]. Gopinath et al [113] noticed the highest enhanced wear resistance in AA6061%-30%BN-10%Al 2 O 3 -5%Gr hybrid composite over all other materials regardless of the test conditions. According to a study by Sharma et al [114], sillimanite-reinforced composite offered enhanced wear resistance over the monolithic alloy.…”
Section: Influence Of Particle Reinforcementmentioning
confidence: 99%
“…A scan rate of 1 mV/s is maintained throughout the experiment. The Electrochemical Impedance Spectroscopy (EIS) test for the Al-5BN-5SiC-RHA hybrid nanocomposites are accomplished at the range of 100 kHz to 100 MHz and at the voltage of 5 mV [25,29,30].…”
Section: Electrochemical Corrosion Analysismentioning
confidence: 99%
“…The ceramic particles such as Al 2 O 3 , ZnO, SiC, B 4 C, BN and TiC are the materials which are explored earlier owing to their exceptional mechanical, electrical properties and also because of their availability [16][17][18]. Further it has also been reported that BN and SiC ceramic particles possesses excellent mechanical and corrosion resistant properties compared to other ceramic particles [8,[19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Different from traditional Al-Mg [18,44] and Al-Mg-Si [45,46] alloys, AMg61 (Al-6.2% Mg) is a newly developed highstrength aluminum alloy with high magnesium content, which is specially used as the key structural material for the high-velocity speedboat. Nevertheless, the high Mg content results in an anodic second phase, which leads to a strong tendency to corrosion in the marine environment.…”
Section: Introductionmentioning
confidence: 99%